Economic designing of high-performance flexible supercapacitor based on cotton leaf derived porous carbon and natural ocean water. (August 2021) - Mao, Yanna; Kumar, Nadavala Siva; Dhar, Abhishek; Poulose, Anesh Manjaly; Kashif, Muhammad; Al-Ghurabi, Ebrahim H.; Asif, Mohammad; Boumaza, Mourad; Duan, Yongtao; Vekariya, Rohit L.
Highlights: Carbonized and activated high specific surface area and micro/mesoporous carbon obtained from the cotton leaves. Flexible supercapacitor fabricated using natural ocean water as an electrolyte. The FSC shows outstanding flexibility and durability upon strong mechanical bending cycles. Cotton leaves derived porous carbon in ocean water electrolyte showed an excellent specific capacitance of 212 F. g −1 . Abstract: Due to our imminent energy need, alternative energy resources are inevitably required to be incorporated into our energy storage devices to fulfill the electricity needs. In this context, carbonized and activated high specific surface area and micro/mesoporous carbon obtained from the cotton leaves have been examined for flexible supercapacitor (FSC) using natural ocean water as an electrolyte. The as-prepared FSC based on cotton leaves-derived porous carbon (CLPC) in Ocean water-electrolyte showed an excellent specific capacitance (Csp) of 212 F. g −1 at 1.0 A. g −1 with outstanding cycling stability of 89% for 5000 cycles at high current density. The FSC shows outstanding flexibility and durability upon strong mechanical bending cycles. Also, CLPC electrodes exhibit a high energy density of 7.36 Wh.kg −1 at a power density of 500 W.kg −1, which is better than those of earlier published similar bio-mass carbon materials, indicating the eye-grabbing significance of abundant and inexpensive ocean water as a natural electrolyte in production of flexible energy storage devices. Graphical abstract: Image, graphical abstract